Social media marketing strategy in small medium tourism enterprise (smtes); a case of step to jump consultancy - Norulhuda Awang (2014)
The case study is dealing with social media and the marketing activities in STJ Consultancy. To be more exact it is dedicated to research the issues arising in run the business as start up an how startup companies can use social media marketing strategy to optimize the resources and to reduces the cost. Social media is a diversified channel of online marketing and it has many different tools. Besides, the case study explains the theoretical background of social media, and it also writes about its relation with other online marketing activities such as Search Engine Optimization (SEO) and blogging